Engineering the proton conductivity of metal–organic hybrid materials by varying the coordination mode of the ligand. Issue 18 (22nd April 2016) - Liu, Bai-Ling; Zang, Hong-Ying; Tan, Hua-Qiao; Wang, Yong-Hui; Li, Yang-Guang
Abstract : We report the adjustment of proton conductivity by varying the coordination mode of a ligand. Abstract : Reports of the design and synthesis of adjustable proton-conducting metal–organic coordination hybrids are still rare. Herein, we synthesized and characterized two coordination compounds: Cu(HL)L (1 ) and H4 Mo8 O24 L4 ·3H2 O (2 ) (L = 4-(1 H -imidazolyl) benzoic acid). In addition, we first report the adjustment of the proton conductivity of metal–organic hybrids via varying the coordination mode of a specific ligand L (L = 4-(1 H -imidazolyl) benzoic acid). Compound1 has a proton conduction of 1.08 × 10 −3 S cm −1 at 97% RH at room temperature, whereas under the same conditions, 2 has an obviously lower proton conduction of 1.09 × 10 −6 S cm −1 . The proton conduction of the two hybrids varied by nearly one thousand fold.